Dilemma of Transitioning from an Educator to Departmental Head in the Foundation Phase, South Africa - Makhananesa Joseph LESIBA; Mmalefikane Sylvia SEPENG (Social Sciences and Education Research Review)
Departmental heads in the Foundation Phase in the South African primary schools are appointed from the ranks of educators and their operation and job descriptions are governed in line with the Personnel Administrative Measures. Bridges' transition theory accentuates the importance of understanding the contexts in which these middle managers operate and provide possible coping mechanisms in the new responsibilities. This article explores the theory as it pertains to Foundation Phase departmental heads who are classroom-based and also have to perform management duties. In conjunction with relevant legislation governing Foundation Phase departmental heads, the study seeks to weigh in on the strengths and weaknesses of the theory along with related literature. This study adopted a qualitative and interpretive approach and involved 18 participants in four categories. These participants were primary school principals, deputy-principals, Foundation Phase departmental heads and their curriculum advisors. Through interviews using purposively sampled schools and officials in Mopani East District in South Africa, the study collected empirical evidence. One remarkable finding was that most of the participants argued that transition and change refer to two different processes. The former involves multiple stages that need precise attention while the latter can be a once-off thing. Bridges' theory fails to outline step-by-step measures that departmental heads can use in order to manage their work environment effectively. The study emphasised the need to introduce scholarships and bursaries for promotion enthusiasts so that they get ready for the new responsibilities in time and execute them with aplomb. Doing so can facilitate effective transition and effectiveness in their work. The importance of collaboration among all stakeholders was also a focal point so that regular monitoring and support programmes in schools can be carried out. The study recommended that the Circuits and the Districts need to champion all management development programmes and initiatives for Foundation Phase departmental heads to bolster their efficiency.